LOCALITY AND STEREOTYPICAL CONCEPTS AS PREDICTORS OF VOTING ATTITUDES AMONG PUBLIC AND PRIVATE ADULT NIGERIAN EMPLOYEES - CHRISTIAN OGBOGU UGOCHUKWU; JACOB IGO; CASMIR NNAEMEKA NWANKWO; BASSY JOHN-JIREH (International Studies Journal)
The study examined the Locality and Stereotypical Concepts as the Predictors of Voting Attitude among Public and Private Adult Nigerians Employees. Locality as an established place one resides, and stereotype originally demoted a solid metallic printing plate containing stock image that is difficult to change once cast was measured with Gender Stereotype Scale (GSS) developed by Sekhar & Parameswari (2020), and voting attitude as the consistent manner of feeling and beliefs of how a person views the electoral process that predispose one to act in a certain way during voting was measured using Attitude to Voting Scale (AVS) developed by Obiechina (2009). Two hypotheses was formulated and tested, two hundred and six (206), (volunteered (62) and drawn (144)) participants using accidental and convenience sampling technique from eight states within four geo-political regions (East, South, West and North) of the country (Anambra, Abia, Cross River, Bayelsa, Ondo, Oyo. Kanu and Kaduna) participated in the study. They were 122 males and 84 females with their age ranged between 27-59 years, average mean age of 30.69 and standard deviation age of 4.63. The study design was cross-sectional, correlational and hierarchical multiple regression analysis was used as the statistical package. Results of the data analysis shows that gender, locality and stereotype significantly (β = .36*; t = 4.09, p< .01; β = .37*; t = 4.66, p< 0.1 and β = .26; t = 4.69, p< .01) predicted the voting attitude of the studied participants. These significant results were discussed alongside with the literature reviewed, implications and recommendation were made.